Analisis Kelayakan Finansial Usaha Perkebunan Karet Rakyat Swadaya di Desa Sungai Jalau Kecamatan Kampar Utara Kabupaten Kampar - Nastalia, Risa Dwi; Tarumun, Suardi; ', Yusmini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this research is to analyze the financial feasibility of rubber plantation in Desa Sungai Jalau, North Kampar district. Desa Sungai Jalau obtain assist production medium from Plantantion Office of Riau for development 35 ha rubbers plant. The instruments of this research are; analyzing the (NPV), (Net B / C) and (IRR) and also sensitivity analysis. The used of data is primary data and secondary data. Primary data is price data were obtained from farmers and employer and secondary data is physics data obtained from Tamora garden of PTPN V, and another data from related agencies. The result shower that analyzing Net Present Value (NPV) is Rp.447.198.856,00, Net Benefit Cost (Net B/C) is 5,41 and Internal Rate of Return (IRR) is 30,48%. The farmer income in one month is Rp. 1.491. 663,00. Analyzing of sensitivity of the changes of the production around 5%,NPV Rp.436.858.726,00 which slope NPV is 2,38%. The changes of the output around 10%, nilai NPV Rp. Rp. 440.909.123,00 which slope NPV is 1,42. The changes of the input around 40% NPV Rp. 203.569.908 which slope NPV is 54,55%.These proofed the rubber plan is still able to do if there is the changes of price and three aspects, because the NPV value still give positive value and IRR value > 0 and also Net B/C bigger than discount factor 12%. Keyword: Rubber, Criterion of Investment, Analyze of sensitivity.